Multi-Agent Reinforcement Learning for Cooperative Air Transportation Services in City-Wide Autonomous Urban Air Mobility - Park, Chanyoung; Kim, Gyu Seon; Park, Soohyun; Jung, Soyi; Kim, Joongheon (IEEE Transactions on Intelligent Vehicles, 2023)
The development of urban-air-mobility (UAM) is rapidly progressing with spurs, and the demand for efficient transportation management systems is a rising need due to the multifaceted environmental uncertainties. Thus, this article proposes a novel air transportation service management algorithm based on multi-agent deep reinforcement learning (MADRL) to address the challenges of multi-UAM cooperation. Specifically, the proposed algorithm in this article is based on communication network (CommNet) method utilizing centralized training and distributed execution (CTDE) in multiple UAMs for providing efficient air transportation services to passengers collaboratively. Furthermore, this article adopts actual vertiport maps and UAM specifications for constructing realistic air transportation networks. By evaluating the performance of the proposed algorithm in data-intensive simulations, the results show that the proposed algorithm outperforms existing approaches in terms of air transportation service quality. Furthermore, there are no inferior UAMs by utilizing parameter sharing in CommNet and a centralized critic network in CTDE. Therefore, it can be confirmed that the research results in this article can provide a promising solution for autonomous air transportation management systems in city-wide urban areas.
Keywords: Air transportation service; Atmospheric modeling; Centralised; Centralized training and distributed execution; Deep learning; Multi agent; Multi-agent deep reinforcement learning; Reinforcement learnings; Transportation services; Urban air; Urban areas; Urban-air-mobility; air transportation service; centralized training and distributed execution (CTDE); multi-agent deep reinforcement learning (MADRL); Urban-air-mobility (UAM)